MIB-1, Ki67, and PCNA scores and DNA flow cytometry in intermediate grade malignant lymphomas. Issue 1 (January 1994) - Pich, A; Ponti, R; Valente, G; Chiusa, L; Geuna, M; Novero, D; Palestro, G
Abstract : AIMS–To verify the correlation between MIB-1, Ki67, and proliferating cell nuclear antigen (PCNA-PC10) scores and S-phase fraction in intermediate grade non-Hodgkin's lymphomas (Working Formulation F); and their reliability in differently processed tissues. METHODS–Forty one non-Hodgkin's lymphomas were classified as (F) intermediate grade malignant lymphomas according to the Working Formulation; mitotic counts and percentage of large cells were assessed for each case. Sections from formalin fixed, paraffin wax embedded tissues were stained with anti MIB-1 monoclonal antibody, after microwave oven processing, and anti-PCNA (PC10) monoclonal antibody using an avidin-biotin immunoperoxidase (ABC) method. One thousand cells from 10 representative fields were scored. Frozen sections from surgical specimens were stained with Ki67 monoclonal antibody using the ABC method; the fraction of Ki67 positive cells was calculated scoring 1000 cells. Flow cytometry analysis (FCM) was performed on cell suspensions from fresh tissues. Correlations between data were estimated using linear regression. RESULTS–A linear correlation was found between MIB-1 and Ki67 scores (r = 0.92; p < 0.00001); between MIB-1 and PCNA scores (r = 0.79; p < 0.00001); and between MIB-1 score and S-phase fraction (r = 0.51; p = 0.0006). A linear correlation was also found between Ki67 and PCNA scores (r = 0.85; p < 0.00001); between Ki67 score and S-phase fraction (r = 0.6; p = 0.0002); and between PCNA score and S-phase fraction (r = 0.74; p < 0.00001). A correlation was found between mitotic counts and MIB-1 (r = 0.56; p = 0.0001), PCNA (r = 0.51; p = 0.0007), or Ki67 scores (r = 0.47; p = 0.002); between the percentage of large cells and MIB-1 (r = 0.49; p = 0.0009), PCNA (r = 0.6; p = 0.00003), and Ki67 scores (r = 0.53; p = 0.0003) and S-phase fraction (r = 0.55; p = 0.0002). CONCLUSION–MIB-1, Ki67, and PCNA (PC10) scores and S-phase fraction are highly correlated and equally well represent the proliferative activity of intermediate grade non-Hodgkin's lymphomas in differently processed material. MIB-1 and PCNA stains can be applied even on small biopsy specimens. MIB-1 produces homogenous staining without background; it also strongly stains mitotic figures. It can be performed on routinely processed tissues, permitting the simultaneous evaluation of the morphology and tumour cell kinetics. The wide standard deviations of the proliferative indices found for intermediate grade NHL suggest that this category probably includes various degrees of malignancy.